Cambodia 1998-2008 : An Episode of Rapid Growth - Guimbert, Stephane (2012)
Cambodia's growth over 1998-2008 has been remarkable (almost 10 percent per annum for a decade). This paper applies a "growth diagnostic" approach to understand how this happened and how it can be sustained. Past growth has been driven by the coincidence of a set of historical and geographic factors (including opportunistic policy responses), together with the use of natural assets (although in a non sustainable way) and the elaboration of productive sector-specific governance arrangements. Several of these factors are unfortunately not self-sustaining and the global economic crisis of 2008-09 is exposing these vulnerabilities. A growth diagnostic flags a number of short-term priorities to ensure the competitiveness of existing industries, as well as more medium-term priorities for the country to continue attracting foreign investment and start mobilizing more domestic savings. A key economic policy objective is the diversification of the economy, which requires a reduction in unproductive risks and costs as well as creative solutions to coordination failures.